Development of a pH-sensitive film based on collagen/chitosan/ZnO nanoparticles and mulberry extract for pork freshness monitoring. (15th February 2023) - Zheng, Tingting; Tang, Pingping; Li, Guoying
Highlights: pH-sensitive film based on collagen, chitosan, ZnO-nanoparticles and mulberry extract (CC/ZnO/ME) was developed. CC/ZnO/ME film showed excellent light barrier, mechanical and antioxidant properties. The color of CC/ZnO/ME film changed from red to blue/green as pH value increased from 3 to 12. The pH-sensitivity of CC/ZnO/ME film was affected by ME content. The color of the indicator film turned from deep purple to blue when pork was not fresh. Abstract: pH-sensitive films based on collagen, chitosan, ZnO-nanoparticles and mulberry extract (CC/ZnO/ME) were developed to monitor pork freshness. Fourier transform infrared analysis revealed that collagen, chitosan, ZnO-nanoparticles and ME interacted via hydrogen bonds. The UV–vis light barrier ability of CC/ZnO/ME film was gradually enhanced as increasing ME content from 0.5 to 2.0 % wt. Compared with CC film, the mechanical strength and DPPH radical free scavenging rate of the CC/ZnO/ME film had increased by 13.84 MPa and 58.74 %, respectively. CC/ZnO/ME1 and CC/ZnO/ME2 films exhibited better pH-sensitivity than CC/ZnO/ME3 film, with color visibly changing from red to blue/green in different buffer solutions (pH 3–12). When monitoring the freshness of pork stored at 4℃, the color of CC/ZnO/ME2 film changed from deep purple to blue when TVB-N content exceeded the maximum permissible limit (15 mg/100 g) on 6th day.